2006
DOI: 10.1111/j.1526-100x.2006.00151.x
|View full text |Cite
|
Sign up to set email alerts
|

Macrophytes in Urban Stream Rehabilitation: Establishment, Ecological Effects, and Public Perception

Abstract: Efforts to rehabilitate degraded urban streams generally focus on improving physical habitat and rarely include reestablishing biota such as macrophytes. Our objectives in this study were to propagate and transplant native macrophytes into a South Island, New Zealand, urban stream undergoing rehabilitation, assess macrophyte survival and growth, and determine whether native macrophytes suppress non-native macrophytes and/or enhance stream invertebrate communities. Effects of native macrophytes on invertebrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 45 publications
0
48
0
Order By: Relevance
“…The propagation technique used in our study and in New Zealand (Larned et al 2006) seems to be a success as all plant beds established in the trays. Propagation reduces the risk of losing biomass after planting because a well-developed root system has better anchoring strength.…”
Section: Macrophyte Colonisation and Sustainabilitymentioning
confidence: 90%
See 3 more Smart Citations
“…The propagation technique used in our study and in New Zealand (Larned et al 2006) seems to be a success as all plant beds established in the trays. Propagation reduces the risk of losing biomass after planting because a well-developed root system has better anchoring strength.…”
Section: Macrophyte Colonisation and Sustainabilitymentioning
confidence: 90%
“…Generally, the three basic physical conditions needed for sustainable macrophyte growth are shallow water (\1 m), water velocity(\0.4 m s -1 ) during plant establishment, and unshaded conditions. From our experience we have found that newly created headwater stream reaches and larger stream reaches with initially low plant cover (\10%) re very suitable for establishment of new macrophyte beds (Larned et al 2006;this study). On the other hand, stream reaches with high plant cover and those with high flow variability are less suitable for macrophyte transplantation projects (Suren 2008).…”
Section: Macrophyte Colonisation and Sustainabilitymentioning
confidence: 96%
See 2 more Smart Citations
“…Community-led monitoring programmes involve, educate and empower local communities. Examples of community-scientific monitoring in New Zealand include the Stream Health Monitoring and Assessment Kit (Biggs et al 1998), the national wetland indicators monitoring handbook (Clarkson et al 2002) Larned et al 2006). Identifying synergies between Māori-community monitoring, and scientific and community-scientific approaches may provide a platform to integrate multiple stakeholder views into resource management and policy development.…”
Section: Introductionmentioning
confidence: 99%